Βιβλιογραφικά: Προσθήκες, συμπληρώσεις και διορθώσεις στην Ελληνική Βιβλιογραφία (17ος-19ος αι.) - Melianos, Ioannis M. (The Gleaner, 2024)
Additions, Supplements and Corrections to the Greek Bibliography (17th-19th Centuries) The aim of this article, which presents some titles of old printed books, is to offer additions, supplements, and corrections to the Greek Bibliography (17th-19th centuries). The list of these titles is based mainly on the book collection of the convent of Zoodochos Pigi in Chora, Patmos, which has been recently inventoried. Furthermore, it is supplemented by a number of entries from the library of the Monastery of Saint John the Theologian. From these forty-eight entries, the first six concern uncatalogued editions –hence they are additions to the Greek Bibliography (one is an 18th century-edition, while the rest five date from the second half of the 19th century). As for the remaining forty-two entries, they are additions, corrections and remarks on editions known in the bibliography (17th-19th centuries). The entries concerning the uncatalogued editions are presented in full, while those of already known publications are presented in an abbreviated form, with the exception of those cases where the titles have been incorrectly catalogued. All entries include the precise number of folios or pages, and, when necessary, they present a detailed description of the contents, as well as further information. For all the cases in hand research and cross-checking have been conducted in the known printed bibliographies, as well as in the up-to-date electronic catalogue of the Greek Bibliography of the 19th century, provided by the Bibliology Workshop “Philippos Iliou”.